Konsep kesejahteraan melalui produksi Islam: Sebuah tinjauan literatur - Dynika, Irfani Robbeth (Maliki Interdisciplinary Journal, 2024)
This journal discusses the concept of welfare in an Islamic perspective through production based on sharia principles. Welfare (falaḥ) is not only measured from the material aspect, but also includes spiritual and moral dimensions, which are rooted in devotion to Allah. Production in Islamic economics is seen as a means to achieve holistic welfare, where every production activity must provide benefits to society and not only be orientated towards individual profit. It emphasises the importance of ethics and morality in production activities, as well as social responsibility to ensure people’s basic needs are met. It provides insights into how the integration of production and spiritual values in Islam can create balanced and sustainable prosperity. The research encourages economic actors to not only focus on material gains, but also consider the social and environmental impacts of their activities. As such, prosperity in the Islamic context can be achieved through wise and responsible resource management